A Learning Missional Church : Reflections from Young Missiologists. - Fagerli, Beate (Edinburgh Centenary., 2012)
Cross-cultural mission has always been a primary learning experience for the church. It pulls us out of a mono-cultural understanding and helps us discover a legitimate theological pluralism which opens up for new perspectives in the Gospel. Translating the Gospel into new languages and cultures is a human and divine means of making us learn new 'incarnations' of the Good News.